2023
DOI: 10.12659/msm.940889
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Cinobufagin

Abstract: Cinobufagin (CBF) is a bufadienolide, which is a major active ingredient of toad venom. In recent years, CBF has attracted increasing attention due to its highly potent and multiple pharmacological activities. To better understand the status of research on CBF, we collated recent studies on CBF to provide a valuable reference for clinical researchers and practitioners. According to reports, CBF exhibits extensive pharmacological properties, including antitumor, analgesic, cardioprotection, immunomodulatory, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Figure B). Since its isolation in 1932 by Jensen, numerous studies have explored its medicinal properties and demonstrated its clinical significance . In addition to inhibiting Na + ,K + -ATPase, cinobufagin has been shown to regulate secretion of aldosterone and cortisol and StAR gene expression as well as induce cell cycle arrest and apoptosis in tumor cells.…”
mentioning
confidence: 99%
“…Figure B). Since its isolation in 1932 by Jensen, numerous studies have explored its medicinal properties and demonstrated its clinical significance . In addition to inhibiting Na + ,K + -ATPase, cinobufagin has been shown to regulate secretion of aldosterone and cortisol and StAR gene expression as well as induce cell cycle arrest and apoptosis in tumor cells.…”
mentioning
confidence: 99%